Knowledge Improvement on Oral Hygiene Through Dental Health Education Program - Darmadi, Eveline Yulia; Ameliana, Yemy; Fauziah, Yessy Andriani; Widjaja, Jennifer (Universitas Lambung Mangkurat, 2025)
Dental caries remains one of the most prevalent chronic diseases, especially in developing countries like Indonesia. In Desa Randegansari, East Java, low awareness and poor oral hygiene contribute significantly to its high incidence. This community service program aimed to improve oral hygiene knowledge among adult residents in Desa Randegansari through a single-session education using the Participatory Action Research (PAR) approach. The session focused on key preventive topics, including the frequency and technique of toothbrushing, appropriate brushing duration, the effects of sugary foods, and common risk factors for dental caries. Before and after the session, participants completed a standardized questionnaire to assess changes in knowledge. Participants completed a questionnaire before and after the session. Results showed increased knowledge, particularly in brushing frequency (47.37% to 68.42%) and duration (36.84% to 63.16%), though understanding of the effects of sugar consumption declined slightly (89.47% to 73.68%). The number of participants answering all questions correctly rose from 0% to 21.05%. The results showed a notable increase in the number of correct responses after the session, indicating that even a single educational intervention can significantly enhance public awareness and understanding of oral health. This program highlights the effectiveness of a participatory, context-based educational model designed for rural populations with limited access to dental care. This approach helped rural communities build on existing knowledge while learning healthier habits. It proves that small, focused efforts can lead to meaningful improvements in public health awareness.